No Spread of SARS-CoV-2 From Infected Symptomatic Children to Parents: A Prospective Cohort Study in a Controlled Hospital Setting - Nunziata, Francesco; Poeta, Marco; Vassallo, Edoardo; Continisio, Grazia Isabella; Lo Vecchio, Andrea; Guarino, Alfredo; Bruzzese, Eugenia (Frontiers in Pediatrics, 2021)
Introduction: The transmission rates severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) from children to adults are unclear due to a lack of controlled conditions. Materials and methods: We investigated the occurrence of SARS-CoV-2 transmission among 12 discordant child-parent pairs in our ward. In each hospital isolation room, caregivers and children lived in close contact during the entire hospitalization period. Results: A total of 136 swab-positive children (mean age, 3.6 ± 4.9 median age, 1; IQR 0-6.2, range 0.1-17) attended by their caregivers were hospitalized. Of those, 12/136 (8.8%, mean age, 6.1 ± 5.3 median age, 4.5) were attended by caregivers who were swab and serology negative at admission despite previous close contact with positive children at home. Three children were completely dependent on their mothers, one of whom was being breastfed. The mean duration of overall exposure to the index case was 20.5±8.2 days. Conclusion: None of the infected children transmitted SARS-CoV-2 infection to their caregivers, raising the hypothesis of a cluster of resistant mothers or of limited transmission from children to adults despite prolonged exposure and close contact. These data might provide reassurance regarding school openings and offer the chance of investigating SARS-CoV-2 variants in the future under the same quasi-experimental conditions.